Mental health of religious/spiritual lesbians, gays and bisexuals: a scoping review - Ágatha Aila Amábili de Meneses Gomes; Luana Elayne Cunha de Souza; Bruno Ponte Belarmino Lima (Estudos de Psicologia (Campinas))
Abstract Objective The effects of religiosity and spirituality on the mental health of Lesbians, Gays and Bisexuals are not clear, especially when there is an incongruity between religious/spiritual beliefs and sexual orientation. Based on this ground, a scoping review was performed to map the evidence reported in the literature on the relationship between religiosity/spirituality and mental health in religious/spiritual lesbians, gays and bisexuals. Method The search was performed using the PubMed, PsycINFO, Web of Science, Scientific Electronic Library Online and Literatura Latino-Americana e do Caribe em Ciências da Saúde databases and a total of 36 studies were selected for review. Results It was found that religiosity and spirituality can be both beneficial and harmful to the individuals assessed, as there was no consensus regarding their effect on mental health. Conclusion In general, this review offers contributions to the scientific knowledge, pointing out the complexity of the phenomenon and the existing gaps in studies already carried out, allowing the establishment of directions for future research.